Design and Construction of a SaaS-Based Multi-tenant Information System for Drone Activity Recording and Inventory - I Wayan Juli Budiarta; Ida Bagus Ary Indra Iswara; I Made Sukafona; Ni Wayan Sumartini Saraswati; I Putu Agus Eka Darma Udayana (JST (Jurnal Sains dan Teknologi), 2026)
Drone flight activity and inventory recording in uncrewed aerial vehicle (UAV) service providers is still dominated by manual methods and separate local systems. This condition risks recording errors and hinders operational data integration and access. This study aims to develop a SaaS-based multi-tenant information system for drone activity and inventory recording. This type of research is Research and Development with a Rapid Application Development (RAD) design. The research subjects included one drone company owner to inform the formulation of system requirements, while the researcher conducted trials independently using an access load simulation. Data were collected through interviews, observations, and literature reviews, with Apache JMeter as the testing tool and the stress testing method. Data analysis was conducted descriptively and qualitatively. The results of the study show the system is stable at low to medium loads and remains functional at high loads despite performance degradation. The study's conclusions indicate that the system can replace manual recording in web-based drone operational management. This study provides an overview of the application of a multi-tenant SaaS architecture to support centralized drone flight and inventory data management, while ensuring security and data isolation between organizations.